Proceso atención de enfermería en gestante de 26 semanas con amenaza de parto prematuro por incompetencia cervical uterina. - Salazar Echeverria, Camila Alexandra (2025)
This clinical case study is applied to a female patient with 26 weeks of gestation due to LMP, who presented a clinical picture of vaginal bleeding showing 30 ml in a sanitary pad, abdominal pelvic pain with contractions plus lower back pain on the EVA scale of 8/10, leucorrhea, hydrorrhea and asthenia. A peripheral line was placed for the administration of pharmacological treatment. A cephalocaudal assessment was performed, where a single live product was confirmed, cephalic longitudinal, right back and fetal movements were present, and altered functional patterns of Marjory Gordon were identified, which were compromising the maternal-fetal status. These were treated immediately by the nursing staff through the Nursing Care Process and its NANDA, NOC and NIC taxonomies. Tests such as a complete blood count and abdominal pelvic ultrasound were also performed to determine the status of the product. The pregnant woman was hospitalized in the gynecology area, to provide her with greater control and nursing care during her hospitalization.